Perancangan Sistem Informasi Absensi Dan Cuti Karyawan Pada PT. Pinus Merah Abadi - prasetyo, hendra; Komarudin, Rachman (Universitas Islam Syekh Yusuf, 2021)
Attendance and employee leave are important factors for an agency or company to achieve goals, this is related to discipline and has an impact on the performance of each employee. Therefore, it is necessary to have special data collection to record employee leave, employee overtime and attendance and absence so that work activities can be recorded in real time and properly. There are many ways that can be done to achieve a good attendance information system, one of which is using personal computer technology where its application is website-based attendance software. At the office of PT. Pinus Merah Abadi system used in the attendance process is still manual using daily attendance papers, leave and overtime which have an impact on the efficiency and effectiveness of data collection, data search as well as data recap calculations which take a relatively long time. Meanwhile, the risk of errors and loss of attendance data is getting bigger. Based on the above problems, an information system for attendance, leave and employee overtime was made at the PT. Pinus Merah Abadi. The research method is the method used in data collection which includes: research methods, interviews and literature. While software development using waterfall which includes: needs analysis, design, coding, testing and implementation. With the production of employee leave applications, employee overtime and employee attendance based on the website, it can provide convenience in the process of employee leave, employee overtime and attendance, data search and recapitulation of employee leave, employee overtime and attendance, as well as minimizing losses and errors in recording employee leave data, overtime employees and attendance at the office of PT. Pinus Merah Abadi.